Payment Information System For Acceptence New Students Using Virtual Account - abdul latif (NAROTAMA UNIVERSITY, 2021)
With the development of information technology that is so fast today, inevitably all aspects of life, including educational institutions, must follow. The university has also started implementing new student admissions through online media, from the registration process, payments, entrance tests and announcements of being accepted or rejected. In its implementation, find obstacles, how is the payment system? if you use a transfer, it's hard to tell which one pays the registration fee and the others. After discussing with the leadership, marketing team and the bank, it was decided to use the virtual account (VA) method. The author then analyzes and designs an online new student admission payment information system using the virtual account (VA) method. The case study adopted in this study at the Merdeka University, Surabaya. Previously, new student admissions were carried out directly on campus, but in the current pandemic season, it is not possible for prospective students to come to campus considering the danger of covid is still very dangerous. Therefore, it is very appropriate if at this time Merdeka University Surabaya had to change the system from prospective students registering to come to campus using online media. The method that the author uses in making this application with the waterfall, starting from the study of literature, analysis, design and implementation of the program. For registration and entrance test, the author uses web media and for payment processing the author uses the virtual account (VA) method.